Confabulation or hallucination? A case of bilateral occipital infarct blurring the boundaries between Charles Bonnet and Anton’s syndromes - Killian Welch (Advances in Clinical Neuroscience & Rehabilitation)
We present the case of a 53 year old man with severe visual impairment after an acquired brain injury who experienced erroneous visual perceptions. These experiences had features of both Charles Bonnet and Anton’s syndromes, two conditions traditionally differentiated by the presence or absence of insight. We believe this case provides a window into the processes underpinning perception generation and suggests the boundaries between these two presentations may be looser than is generally thought.